2018
DOI: 10.1007/s00520-018-4417-5
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Collaborative Registry informs understanding of factors predicting sleep quality

Abstract: Results confirm previously identified risk factors and reveal inconsistencies in other variables. Clinicians need to routinely screen for the identified risk factors of self-reported poor sleep quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 41 publications
(69 reference statements)
1
17
0
Order By: Relevance
“…The factors associated with sleep disturbances in cancer patients remain unclear. Previous studies have elaborated that age, higher body mass index (BMI), cancer-related fatigue, depression, and anxiety had a significant association with poor sleep quality among cancer patients ( 14 , 15 ). However, most of the studies focused on the sleep quality of patients before the start or after the end of chemotherapy at present, and studies regarding radiotherapy were less elaborated.…”
Section: Introductionmentioning
confidence: 99%
“…The factors associated with sleep disturbances in cancer patients remain unclear. Previous studies have elaborated that age, higher body mass index (BMI), cancer-related fatigue, depression, and anxiety had a significant association with poor sleep quality among cancer patients ( 14 , 15 ). However, most of the studies focused on the sleep quality of patients before the start or after the end of chemotherapy at present, and studies regarding radiotherapy were less elaborated.…”
Section: Introductionmentioning
confidence: 99%
“…A cross-sectional feasibility study design was used. The parent study examined data from the Breast Cancer Collaborative Registry (BCCR) questionnaire to understand risk factors predicting sleep quality in patients with breast cancer [20].…”
Section: Methodsmentioning
confidence: 99%
“…Measures of physical and mental health status and subjective sleep quality complete the questionnaire. More information about the BCCR is published [20]. All participants completed the BCCR questionnaire either at a clinic appointment or at home and returned it by United States Postal Service.…”
Section: Methodsmentioning
confidence: 99%
“…Patient characteristics may also be associated with sleep disturbance in patients with cancer. Younger age has been associated with increased sleep disturbance [15,[22][23][24], although other studies have found no association between age and sleep disturbance in patients with breast cancer [1]. Additionally, a large (n=12,098) longitudinal study found that breast cancer diagnosis was not signi cantly related to decreased sleep quality compared to pre-diagnosis, although sleep quality continued to decrease over time [25].…”
Section: Introductionmentioning
confidence: 96%
“…Nausea is also a signi cant predictor of cancer-related fatigue, a relationship mediated by the effect of nausea on sleep disturbance [13]. Poor sleep quality has also been associated with lower functional status and decreased quality of life in individuals with a cancer diagnosis [14][15].…”
Section: Introductionmentioning
confidence: 99%